Mesenchymal stem cells ex vivo cultivation technologies for clinical use - T. V. Shamanskaya; E. Yu. Osipova; S. A. Roumiantsev (Онкогематология)
Now mesenchymal stem cells (MSC) are more widely applied in different areas of medicine. However, despite requirement for considerable quantities of human MSC for clinical practice, there is restricted information concerning culture conditions optimization required for their production. In present article the literature review, concerning various conditions of MSC extraction and culture, is presented. Influence of culture medium, cells passage density, fetal calf serum presence or absence and other conditions on MSC proliferation is surveyed. Data concerning use of three-dimensional structures and various bioreactors for ex vivo expansion are presented. MSC multilinear differentiation features are surveyed.